Pengenalan Konservasi Melalui Program Forester Education di Desa Jerukwangi, Kecamatan Bangsri, Kabupaten Jepara - Alifah Fidela; Muslimatul Rahmi; Istie Sekartining Rahayu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Conservation education is a program that is packaged with the aim of providing knowledge to the younger generation to be more aware and more concerned about the environment and problems and their interrelationships. The purpose of this program is to introduce conservation through the Forester Education program in Jerukwangi Village. This activity was applied in two methods of implementation, namely formal and informal. The method of implementation was formally implemented in State Elementary School 2 by providing material exposure, while the method of implementation was informally carried out at the community service post in Jerukwangi Village with the target of young children using the approach of playing while drawing. Both formal and informal provision of material has given children knowledge about the importance of ecosystem balance that needs to be maintained. The results of this activity are the embedded spirit of protecting the environment from an early age, starting with good habits such as throwing trash in its place, protecting and caring for plants, learning to make chains and food webs, as well as various activities that hone soft skills and character education. Keywords: Conservation, ecosystem, forester education